Diagnostic approaches to transboundary and zoonotic diseases - Bold, Dashzeveg (My University, 2025)
Transboundary animal diseases (TADs), including those caused by African swine fever virus (ASFV), Classical swine fever virus (CSFV), and Foot-and-mouth disease virus (FMDV), as well as highly contagious zoonotic agents such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), pose significant threats to agriculture and public health globally. Early detection and follow-up measures are critical for the management of these infectious diseases. In the laboratory, polymerase chain reaction (PCR) is the most commonly used method for diagnosing these pathogens; however, in order to rapidly identify and prevent the spread of these highly infectious viruses, point-of-care (POC) diagnostic assays for the detection of the pathogen’s genetic materials, antigens (Ag), and antibodies (Ab) in the field are necessary. In this dissertation, lateral flow assays (LFAs) for ASFV Ag and Ab detection, multi-antigen print immunoassays (MAPIAs) for ASFV and FMDV Ab detection, and indirect ELISAs for SARS-CoV-2 Ab detection were established. It was also demonstrated that POC approaches used in a low-income country were able to identify ASFV, CSFV, and FMDV genetic sequences in suspect materials, proving the feasibility of POC diagnostics for these pathogens in low resource environments. As a result of this thesis, valuable tools were generated for improving the detection and diagnosis of ASFV, CSFV, FMDV, and SARS-CoV-2.
Keywords: Diagnosis; African swine fever virus; Classical swine fever virus; Foot-and-mouth disease virus; SARS-CoV-2; Transboundary animal diseases